ANALISIS PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA GURU PADA YAYASAN PERGURUAN SULTAN ISKANDAR MUDA MEDAN - victor victor (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2019)
The purpose of this research is to know how big influence of leadership, discipline and compensation against teacher performance at sultan iskandar muda school medan. This research was conducted for 4(four) months, start from April 2019 until August 2019. This research uses non probability methods. Research subjects were conducted at sultan iskandar muda school teachers with a population of 93 people. Population research using the census method. The instrument used is a questionnaire to collect data from variables of leadership, discipline, compensation and teacher performance. Data analysis technique used is validity test, reliability test, descriptive analysis, normality test, multicolinearity test, heterokedastisity test, multiple linear regression analysis, T test, F Test and coefficient determination test. Descriptive analysis results in leadership, discipline and compensation variables are in good category, but performance variable result in very good category. The research results showed that Thitung > Ttabel, and Fhitung (3,820) > Ftabel (2,74) mean leadership, discipline and compensation have a positive and significant impact on teacher performance at sultan iskandar muda school medan. Determination coeffisien (R2) shows that independent variables can describe employee’s performance for 81,4% meanwhile the rest of 18,6% describe by others independent variables that are excluded in this research such as motivation, job satisfaction, comitment, comunication and others. Based of interpretation determination coeffisien guidelines, there is a significant influence between the independent variables on the dependent variables.